Game Edukasi Pembelajaran Menghitung Susunan Angka Pada Puzzle-8 Menggunakan Metode Steepest Ascent Hill Climbing - M, Padma Mike Putri (Forum Kerjasama Pendidikan Tinggi, 2021)
Learning games are games that are very much in the interest of preschool children today in carrying out activities because basically, this game playing uses the term play while learning, this game is very useful in brain development for preschool children to increase thinking data in sharpening the brain, this game consists of 8 sequences of numbers that are not sequentially arranged into consecutive numbers to become Puzzled -8 guided by the concept of the rules in the algorithm. The problem, in this case, is the children's lack of interest in learning to count and compile numbers because it is difficult to understand. With the learning game, the aim of this research is to help early childhood children in calculating the sequence of numbers that are usually difficult to understand. This game can be used as a game arena but contains elements of learning and compiling puzzle numbers 8. The method used uses the Ascent Hill Climbing Algorithm which is the process of The work of this algorithm that can produce a regular array of numbers by using the concept of shifting the value of numbers according to the existing rules in the Steepest Ascent Hill Climbing Method algorithm.